Larvicidal Activity of Young and Old Leaves of Ricinus communis linn (Castor) with Ethanol, Aquades, Ethyl Acetate, and N-hexane solvents against Aedes sp. - Bambang Dwicahya; A. Arsunan Arsin; Hasanuddin Ishak; Firdaus Hamid; Maria Kanan; Anwar Mallongi; Ida Leida Maria; Agus Bintara Birawida; Muhammad Syahrir (Public Health of Indonesia, 2026)
Background: Dengue fever remains a major public health problem in tropical regions, including Indonesia, where vector control relies heavily on synthetic larvicides that pose environmental and health concerns. Plant-based larvicides have emerged as promising alternatives; however, comparative evidence regarding the influence of solvent polarity and leaf developmental stage on larvicidal efficacy remains limited. Objectives: This study evaluated the larvicidal activity of young and old castor bean leaf extracts obtained using different solvents against Aedes sp. larvae. Method: A laboratory-based experimental study was conducted following WHO guidelines for mosquito larvicide testing. Young and old leaves of castor were extracted separately using n-hexane, ethyl acetate, ethanol, and distilled water through multistage maceration. Third-instar Aedes sp. larvae were exposed to graded concentrations (75–200 ppm) of each extract, with 25 larvae per treatment and three replications. Larval mortality was recorded hourly for 24 hours. Probit analysis was used to determine LC₅₀ and LC₉₀ values with 95% confidence intervals, and differences among treatments were analyzed using one-way ANOVA (p < 0.05). Results: All extracts exhibited larvicidal activity against Aedes sp., with efficacy varying according to solvent type and leaf age. Ethanol extracts of old leaves produced the highest larval mortality, while ethyl acetate extracts of young leaves showed the lowest LC₅₀ values. Phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, tannins, and steroids in most extracts. LC₅₀ values ranged from 131.403 to 410.225 ppm, whereas LC₉₀ estimates were substantially higher and exceeded the tested concentration range, indicating extrapolation beyond observed data.  Conclusion: The larvicidal effectiveness of castor leaf extracts against Aedes sp. is influenced by both solvent polarity and leaf developmental stage. Old leaves extracted with ethanol and young leaves extracted with ethyl acetate demonstrated comparatively higher larvicidal potential. These findings support the potential of castor as a botanical larvicide, although further studies incorporating standard larvicide controls, quantitative phytochemical analysis, and field validation are required before operational application.   Keywords: Aedes sp; ricinus communis linn; castor